1997
DOI: 10.1517/13543784.6.4.389
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-D-aspartate antagonists for stroke and head trauma

Abstract: The N-methyl-D-aspartate (NMDA) receptor is a ligand-gated ion channel which is widely distributed in the central nervous system (CNS), and which mediates most of the fast excitatory neuronal transmission in the CNS. As with other ligand-gated ion channels, the NMDA receptor is a macromolecular complex which possesses a number of intricate regulatory sites within and around a central ion channel. The key regulatory components for which prototypic antagonists have been developed are the competitive NMDA antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…As glutamate is an essential mediator of neuronal cell death in this model, specific receptor blockers are thought to selectively interrupt postischemic excitotoxicity. As a consequence, high hopes had been associated with the design of novel NMDA receptor antagonists, including selfotel, aptiganel, and gavestinel (Omae and others 1996;Wood and Hawkinson 1997;Farin and Marshall 2004;Wood 2005). The efficient chemical design of these antagonists yielded excellent ligand binding properties at the glycine site of the NMDA receptor.…”
Section: Ischemia Trauma and Epilepsy: Conditions Of Acute Cell Lossmentioning
confidence: 99%
“…As glutamate is an essential mediator of neuronal cell death in this model, specific receptor blockers are thought to selectively interrupt postischemic excitotoxicity. As a consequence, high hopes had been associated with the design of novel NMDA receptor antagonists, including selfotel, aptiganel, and gavestinel (Omae and others 1996;Wood and Hawkinson 1997;Farin and Marshall 2004;Wood 2005). The efficient chemical design of these antagonists yielded excellent ligand binding properties at the glycine site of the NMDA receptor.…”
Section: Ischemia Trauma and Epilepsy: Conditions Of Acute Cell Lossmentioning
confidence: 99%
“…Because of this, a significant amount of time and effort has gone into developing clinically useful NMDAR antagonists. However, while many of these antagonists successfully reduced or eliminated damage in animal models, all failed in clinical trials, in large part due to their unacceptable side effects, including psychosis (Wood PL, 1997; Lai et al, 2011). This double-edged sword demonstrates the importance of carefully calibrated NMDAergic activity in normal neurologic function.…”
Section: Anti-nmdar Encephalitismentioning
confidence: 99%
“…Physiologically, a blockade of at least one of these sites terminates the channel opening of the NMDA receptor to prevent Ca 2+ influx. However, several studies have demonstrated that a compound which would act as a glycine site antagonist might be superior to an NMDA competitive antagonist and a channel blocker with respect to the therapeutic index [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%